Hemophagocytosis induced by Leishmania donovani infection is beneficial to parasite survival within macrophages. - Ayako Morimoto; Kazuyuki Uchida; James K Chambers; Kai Sato; Jing Hong; Chizu Sanjoba; Yoshitsugu Matsumoto; Junya Yamagishi; Yasuyuki Goto (Public Library of Science (PLoS), 2019)
Visceral leishmaniasis (VL) is caused by parasitic protozoa of the genus Leishmania and is characterized by clinical manifestations such as fever, hepatosplenomegaly and anemia. Hemophagocytosis, the phenomenon of phagocytosis of blood cells by macrophages, is found in VL patients. In a previous study we established an experimental model of VL, reproducing anemia in mice for the first time, and identified hemophagocytosis by heavily infected macrophages in the spleen as a possible cause of anemia. However, the mechanism for parasite-induced hemophagocytosis or its role in parasite survival remained unclear. Here, we established an in vitro model of Leishmania-induced hemophagocytosis to explore the molecules involved in this process. In contrast to naïve RAW264.7 cells (mouse macrophage cell line) which did not uptake freshly isolated erythrocytes, RAW264.7 cells infected with L. donovani showed enhanced phagocytosis of erythrocytes. Additionally, for hemophagocytes found both in vitro and in vivo, the expression of signal regulatory protein α (SIRPα), one of the receptors responsible for the 'don't-eat-me' signal was suppressed by post-transcriptional control. Furthermore, the overlapped phagocytosis of erythrocytes and Leishmania parasites within a given macrophage appeared to be beneficial to the parasites; the in vitro experiments showed a higher number of parasites within macrophages that had been induced to engulf erythrocytes. Together, these results suggest that Leishmania parasites may actively induce hemophagocytosis by manipulating the expression of SIRPα in macrophages/hemophagocytes, in order to secure their parasitism.